Risk factors for impaired CD4+ T‐cell reconstitution following rabbit antithymocyte globulin treatment in kidney transplantation. (27th December 2013) - Longuet, Hélène; Sautenet, Bénédicte; Gatault, Philippe; Thibault, Gilles; Barbet, Christelle; Marliere, Jean‐Frédérique; Halimi, Jean‐Michel; Lebranchu, Yvon; Baron, Christophe; Büchler, Matthias
Summary To describe long‐term CD4+ T‐cell reconstitution after rabbit antithymocyte globulin (rATG) treatment and identify predictive factors following kidney transplantation. A single‐center retrospective study analyzed lymphocyte subsets in rATG‐treated kidney transplant recipients (1986–2009). 589 patients were analyzed (maximum follow‐up 21 years). A comparator group (n = 298) received an anti‐IL‐2 receptor monoclonal antibody. CD4+ T‐cell lymphopenia (<200/mm3) was present in 48.5%, 9.2%, 6.7%, 2.0%, and 0% of patients at one, three, five, 10, and 20 years post‐transplant, respectively. CD4+ T‐cell count increased during the first 10 years but remained below the pretransplant count even after 20 years. At 1, 3, and 6 months post‐transplant, mean CD4+ T‐cell count was significantly lower in patients with CD4+ T‐cell lymphopenia at 12 months versus patients without lymphopenia. On multivariate analyses, significant independent predictors for long‐term impaired CD4 T‐cell reconstitution were recipient age, pretransplant CD4+ T‐cell count, 12‐month CD4+ T‐cell count, and tacrolimus or MMF therapy. Recipient age >40 years was identified as a cutoff point. CD4+ T‐cell reconstitution following rATG treatment remains impaired even after 21 years. Most risk factors for long‐term impaired CD4+ T‐cell reconstitution may be evaluated pretransplant or are modifiable post‐transplant.